Recent progress of nanomaterials for diagnosis and treatment of rejection in heart transplantation - Li, Guangyin; Wang, Chun; Ai, Xin; Yang, Yuxi; Yu, Haizhuo; Wu, Piao; Zhao, Weiyi; Tian, Jiawei; Jiang, Shuangquan (Frontiers in Bioengineering and Biotechnology, 2025)
Transplant rejection and the side effects of immunosuppressive therapy have hindered heart transplantation development. Rejection of a heart transplant can lead to cellular and antibody-mediated immunoinflammatory responses and allograft dysfunction, thereby significantly affecting patients’ survival and prognosis. To address these challenges, many new technologies and materials, including nanomaterials, have been developed for potential applications in the heart transplantation field. Nanomaterials are most commonly used as drug delivery carriers, and the addition of specific ligands can enhance drug utilization, strengthen therapeutic effects, and reduce the occurrence of adverse reactions. In addition, nanomaterials have been developed as targeted molecular probes to support various imaging techniques and to assist in monitoring the infiltration of immune cells (such as T cells and macrophages) into cardiac tissue, thus facilitating the early diagnosis of acute rejection (AR). Continuous advances in nanotechnology have led to the development of “theranostic” and intelligent-response nanomaterials for precise disease diagnosis and simultaneous treatment. Nanomedicine primarily relies on the development of Nanomaterials and nanostructured surfaces, along with the application of nanotechnology, for molecular diagnosis, therapy, monitoring, and disease treatment. In this review, we examine the recent development of nanomaterials for the diagnosis and treatment of AR in heart transplantation, and discuss the challenges and future directions for the clinical translation of nanomaterials in heart transplantation.